Molecular insights and antibiotic resistance genes characterization in clinical Vibrio cholera isolates from patients in Peshawar, Pakistan - Muhammad Atif; Jawad Ahmad; Aisha Irfan; Hafiza Misbah Ahmad; Aiman Waheed; Khalid Khan; Numan Fazal (Molecular Biology Reports, 2026)

From cratonic interiors to deltaic shores: Tectonic and paleoclimatic influences on the diagenetic evolution of Khewra Sandstone, Salt Range, Pakistan - Muhammad Ajaz Abbasi; Imran Khan; Atif Iqbal Abbasi; Muhammad Jamil; Nawaz Ikram; Syed Ahsan Hussain Gardezi; Zulfiqar Haider Awan; Umair Aftab Choudary; Abdul Wali Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

A sustainable mechanical engineering framework for biomaterials in healthcare system development - Helal Uddin; Laraib Zanib; Izzah Atif; Basmalaa Ahmed Thabet; Zaryab Basharat; Muhammad Haris Malik; Faheem Ahmad (Next Research, 2026)

Agrobacterium tumefaciens-mediated stable transformation of CP4 EPSPS gene conferring glyphosate resistance in Zea mays L - Muhammad Atif; Hammad Ahmed Abbasi; Muhammad Naveed Anjum (Ecological Genetics and Genomics, 2026)

Assessing meteorological influences and predicting PM2.5 using deep learning approach: A case of Asian metropolitan city, Lahore - Amna Rashid; Rana Muhammad Atif (Atmospheric Environment, 2026)

Exogenous salicylic acid induces GluA and PR1a defense genes and enhances tomato tolerance to combined salinity and bacterial canker stress - Jawad Ahmad; Hammad Ahmed Abbasi; Muhammad Atif; Sana Ullah; Abdullah Jalal; Zunaira Azam; Hafsa Bibi (Vegetos, 2026)

Transforming emerging economies for a sustainable future: How leadership, entrepreneurship, and innovation shape the green transition - Chor Foon Tang; Atif Muhammad (Energy Policy, 2026)

Effect of storage conditions on phytochemical characteristics and activities of black tea cultivated from geographically different landscapes - Syed Ali Raza Naqvi; Sumaira Naz; Muhammad Irfan; Ameer Fawad Zahoor; Atif Hussain Randhawa; João Miguel Rocha; Mohamed Fawzy Ramadan (South African Journal of Botany, 2026)

Novel synthesis of a sulfur-magnesium compound fertilizer from magnesium-based flue gas desulfurization byproducts - Weiqiang Zhang; Fien Degryse; Zenglian Qi; Min Wang; Muhammad Atif Muneer; Michael J. Mclaughlin; Liangquan Wu; Zhenya Lu; Fusuo Zhang (Journal of Cleaner Production, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Antibacterial flavonoid derivatives: in silico ADMET, DFT, Molecular Docking, MD Simulation and in vitro verification - Atif Ishfaq; Affifa Tajammal; Riaz Maira; Aisha Waheed Qureshi; Babar Aleeza; Muhammad Asim Raza Basra (In Silico Pharmacology, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Discovery and Functional Evaluation of Enterobacter gossypi sp. nov. (RT) for Salinity Stress Alleviation in Cotton - Abid Ullah; Aqsa Bibi; Ma Yonghui; Muhammad Atif Azeem; Ali Hazrat; Yasir Arafat; Caixia Han; Nigora Kuchkarova; Hua Shao (Journal of Soil Science and Plant Nutrition, 2026)

Pharmaco-therapeutic modulation of the Glo1–Nrf2–RAGE functional network in chronic inflammation: polyphenols in the context of current anti-inflammatory therapy - Sajid Ali; Muhammad Saeed Akhtar; Adnan Amin; Atif Ali Khan Khalil; Wajid Zaman (Inflammopharmacology, 2026)

Comparative effect of malting on nutritional profile, malting properties and structural characteristics of barley, corn, and rice - Husnain Rasheed; Imran Pasha; Muhammad Atif Randhawa; Muhammad Asif Hanif (Cereal Research Communications, 2026)

Geochemical and petrographic insights into the Lumshiwal Formation (NW Himalayas): implications for provenance, paleoclimate, and economic potential - Syed Nohman Gilani; Muhammad Saleem Mughal; Khawaja Umair Majeed; Hammad Tariq Janjuhah; Yongzhi Wang; Muhammad Atif Bilal; Ahmer Bilal; Syed Wajee-Ul Hassan Gillani; Muhammad Hafeez (Carbonates and Evaporites, 2026)

Green-Synthesized Gold Nanoparticles from Fortunella Margarita (Kumquat) Leaf Extract for Broad-Spectrum Antifungal Control of Postharvest Fruit Crop Pathogens - Bismillah Mubeen; Ammarah Hasnain; Haider Ali; Muhammad Nadeem Khan; Maymoona Saher; Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2026)

Light and temperature differentially influence morphology, phytohormone profiles, and phenolic acid biosynthesis in Allium sativum across developmental stages - Muhammad Jawaad Atif; Bakht Amin; Muhammad Imran Ghani; Muhammad Ali; Zhihui Cheng (Biologia, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Enhancing Soil and Atmospheric Carbon Regulation Through Bombax Ceiba-Based Agroforestry in Drylands - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Atif Latif; Muhammad Azeem Sabir; Muhammad Azeem Akhter; Shafeeq Ur Rahman; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

Rethinking lice management at the human–animal interface: challenges, green alternatives, and the road ahead - Rimsha Jamil; Muhammad Imran; Muhammad Adnan Sabir Mughal; Rao Zahid Abbas; Muhammad Umar Ijaz; Muhammad Kasib Khan; Asghar Abbas; Farhan Ahmad Atif; Sultan Ali (International Journal of Tropical Insect Science, 2026)

Retraction notice to ‘In-house fabrication of macro-porous biopolymeric hydrogel and its deployment for adsorptive remediation of lead and cadmium from water matrices’ [Environ. Res. 214 (2022) 113790] - Muhammad Khalid Azeem; Muhammad Rizwan; Atif Islam; Atta Rasool; Shahzad Maqsood Khan; Rafi Ullah Khan; Tahir Rasheed; Muhammad Bilal; Hafiz M.N. Iqbal (Environmental Research, 2026)

Photo-activated defect engineering unlocks high-performance proton transport in garnet electrolytes - Bushra Bibi; Atif Nazar; Muhammad Yousaf; Tanveer Farid; Rizwan Raza; Syed Asad Abbas Bukhari; Muhammad Faisal Anawar; Kashif Nazar; Hafsa Mansha; Yuzheng Lu; Bin Zhu (Chemical Engineering Journal, 2026)

Redundancy‐Resilient Multi‐Criteria Multi‐Model Ensemble Framework for Drought Assessment Under Climate Change - Hussnain Abbas; Muhammad Shakeel; Zulfiqar Ali; Rizwan Niaz; Naim Ahmad; Ali Atif Yassin Ali (International Journal of Climatology, 2026)
Reliable assessment of drought risks under climate change requires robust evaluation of climate models, redundancy‐resilient ensemble construction, and accurate quantification of extremes. Existing approaches often fail to account for non‐linear dependencies, inter‐model redundancy, and spatial performance, limiting the reliability of drought projections. This study introduces Integrated Information‐theoretic redundancy‐resilient ensemble and drought assessment (IIREDA), a multi‐criteria framework that integrates information‐theoretic dependence measures, redundancy adjustment, spatial performance consistency, and advanced ensemble techniques. Applying IIREDA to 22 CMIP6 global climate models (GCMs) across 29 grid stations in drought‐prone Balochistan (1950–2014; projected SSP1–2.6, SSP2–4.5, SSP5–8.5 for 2015–2100), we identify high‐performing models (e.g., CNRM‐CM6‐1‐HR, MIROC‐ES2L) and highlight underperforming models (e.g., CanESM5‐CanOE). Using the novel HC‐GDM ranking, an optimal subset of 11 GCMs is selected, ensuring robust ensemble construction. Ensemble experiments demonstrate that constrained least squares ensembles (CLSE) outperform equal‐weighted, machine learning and probabilistic methods by reducing bias and effectively managing outliers. For drought characterisation, K‐component Gaussian mixture modelling (K‐CGMM) captures extremes more accurately than traditional univariate distributions. Drought assessment using the proposed IW‐GSPI reveals stable conditions under SSP1–2.6, intensification under SSP2–4.5, and persistent multi‐year severe droughts under SSP5–8.5, further supported by Markov chain analysis. In summation, IIREDA advances methodological rigour in climate risk assessment, providing redundancy‐resilient, probabilistic drought projections to inform mitigation and adaptation strategies.

Facile fabrication of NiO/MnO2/CuO nanocomposite as robust electrode material for electrochemical water splitting - Atif Nazir; Chanda Sehar; Muhammad Fahad Saeed; Areej Fatima; Wael dheaa Kadhim; Zainab Ahmed Abass; Imran Shakir; Aboud Ahmed Awadh Bahajjaj; Muhammad Ali Khan; S. Shah (Fuel, 2026)

Alleviation of Lead Stress in Maize Plants Through the Application of Green-Synthesized Zinc Oxide Nanoparticles - Haseeba Maryam; Nasir Masood; Muhammad Waseem; Temoor Ahmed; Muhammad Zia-ur-Rehman; Muhammad Atif Irshad; Saher Javed; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2026)

Retraction Note: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2026)

Health implications and toxicokinetics of short-term graded dietary exposure of Ochratoxin A in dairy cows - Felipe Penagos-Tabares; Ratchaneewan Khiaosa-Ard; Barbara Streit; Emmanuela Gabara; Siska Aditya; Atif Rana-Muhammad; Mubarik Mahmood; Raul Rivera-Chacon; Johann Huber; Johannes Faas; Shreenath Prasad; Qendrim Zebeli; et al. (The Veterinary Journal, 2026)

Investigation of photocatalytic efficiency and antimicrobial activity via Mn doped SnO2 using an eco-friendly green synthesis method - Laraib Bibi; Tahir Iqbal; Mariam Seemab; Sumera Afsheen; I.M. Ashraf; Faiza Saeed; Atif Mossad Ali; Muhammad Yousaf; M.A. Sayed (Journal of Environmental Chemical Engineering, 2026)

Disordered Pr-alumina: Enabling fast proton dynamics across energy systems - Hafsa Mansha; Touseef Ahmad; Kashf Zaman; Sajid Rauf; Muhammad Khalid; M.Ahsan Masood; Shahzad Rasool; Atif Nazar; Bushra Bibi; Nawal K. Almaymoni; Yuzheng Lu; Jun Wang; et al. (Fuel, 2026)

Aflatoxin surveillance in Punjab’s dairy sector: feed and milk contamination - Naveed Akbar; Farhan Saeed; Muhammad Atif Randhawa; Sanaullah Iqbal; Asif Meraj; Abhayveer Singh; Bushra Niaz; T. Krithiga; Rajashree Panigrahi; Amara Rasheed; Zunaira Basharat; Muhammad Afzaal; et al. (Mycotoxin Research, 2026)

Antibacterial Activity of Anthraquinones Isolated from Reynoutria Japonica Against Staphylococcus aureus: An in Silico and In Vitro Approach - Iqra Anam Khawaja; Sajid Ali; Muhammad Faheem; Syed Babar Jamal; Adnan Haider; Falak Niaz; Mi-Jeong Ahn; Mutiullah Khattak; Atif Ali Khan Khalil (Journal of Pharmaceutical Innovation, 2026)

Phytochemical Profiling and Evaluation of the Anti-inflammatory and Antinociceptive Effects of Lilium polyphyllum Bulb Using In Silico, In Vitro and In Vivo Models - Haider Ali; Shafiq Ur Rahman; Umair Sayad; Atif Ali Khan Khalil; Muzaffar Abbas; Muhammad Shahid (Journal of Pharmaceutical Innovation, 2026)

Thiamine and Indole-3-acetic Acid Mediated Detoxification of Arsenic in Maize to Improve Grain Proximate Components, Yield, and Nutrient Ingredients - Muhammad Atif; Shagufta Perveen; Farah Saeed; Abida Parveen; Sara Zafar; Naeem Iqbal (Water, Air, & Soil Pollution, 2026)

Natural products in medicinal chemistry: targeting inflammatory pathways with plant-derived compounds - Adnan Amin; Muhammad Saeed Akhtar; Atif Ali Khan Khalil; Sajid Ali; Wajid Zaman (Medicinal Chemistry Research, 2026)

Microbial Dream Team: Cotton Performs Better in Salty Soil with Pseudomonas hunanensis RT-12 and Staphylococcus caprae DS-2 - Abid Ullah; Sajjad Ahmad; Muhammad Atif Azeem; Shariat Ullah; Sami Ullah; Muhammad Laiq; Asma Shah; Hua Shao (Current Microbiology, 2026)

From wild ecosystem to the pharmaceutical use–exploring the traditional medicine and socio-cultural heritage of macrofungi from Pakistan - Fahim Hussain Shah; Muhammad Atif Azeem; Tauseef Ullah; Abdul Samad Mumtaz; Sayed Afzal Shah; Muhammad Binyamin Khan; Samantha C. Karunarathna; Abdallah M. Elgorban; Munazza Kiran (New Zealand Journal of Botany, 2025)

Transition of the Karakoram anomaly under emerging hydroclimatic trends - Yasir Latif; Sara C. Pryor; Sardar Ateeq-Ur-Rehman; Sher Muhammad; Muhammad Yaseen; Muhammad Atif Wazir (Science of The Total Environment, 2025)

Electrochemical investigation of bimetallic oxide-carbon composite electrode: Towards enhanced supercapacitor applications - Zaib Ullah Khan; Muhammad Atif (Next Research, 2025)

Influence of superabsorbent polymer and jute covering as internal and external curing techniques on the concrete compressive strength development: Experimental and comparative computational analysis - Umar Khurram Iqbal Khan; Hilal Khan; Atif Mehmood Khan; Hassan Khan; Muhammad Jibran Tariq; Hashim Khan; Muhammad Aamir Khan (Next Research, 2025)

Enhancing environmental quality and mitigating climate change: a renewable energy policy perspective based on evidence from most polluted European countries - Muhammad Sadiq; Muhammad Atif Nawaz; Fengsheng Chien; Arshian Sharif; Sobia Hanif (Gondwana Research, 2025)

The potential influence of food additives and contaminants on the gut microbiota: A comprehensive review - Sana Ullah; Sher Ali; Muhammad Atif; Muhib Ullah; Ghulam Nabi; Lucas Gabriel Dionisio Freire; Eliana Setsuko Kamimura; Amir Sasan Mozaffari Nejad; Carlos Augusto Fernandes de Oliveira (Food and Chemical Toxicology, 2025)

Halotolerant Bacillus Aryabhattai Strain PM34 Mitigates Salinity Stress and Enhances the Physiology and Growth of Maize - Muhammad Atif Azeem; Salman Khan; Fawad Ali; Sajjad Ahmad; Gul Rahim; Muhammad Iftikhar; Majid Iqbal; Rawa Saad Aljaloud; Khaloud Mohammed Alarjani; Hassan Javed Chaudhary (Journal of Plant Growth Regulation, 2025)

Nanostructured Bimetallic Oxide/Graphene Nanocomposites for Next-Generation High-Performance Energy Storage - Zaib Ullah Khan; Jinghua Jiang; Muhammad Atif (International Journal of Environmental Research, 2025)

Exploring the therapeutic potential of Nasturtium microphyllum (Boenn.) Rchb.: a combined in-vitro, in-vivo and in-silico approach - Rabia Khan; Muhammad Musa; Syed Mubassir Shah; Hussan Ara Begum; Alaa S. Alhegaili; Sajid Hussain; Atif Ali Khan Khalil; Sajid Ali (Inflammopharmacology, 2025)

Recent advances in conducting polymers for hybrid solar-driven evaporation systems: Fundamentals, innovations, and applications - Bushra Shakoor; Muhammad Sultan Irshad; Uzma Ghazanfar; Humaira Razzaq; Naila Arshad; Ghazala Maqsood; Iftikhar Ahmed; Muhammad Atif Ali; Muhammad Sohail Asghar; Irshad Hussain; Tao Mei; Tran Vinh Dieu; et al. (Chemical Engineering Journal, 2025)

NiMn-LDH/polypyrrole photothermal structures for interfacial solar steam generation - Ghazala Maqsood; Muhammad Sohail Asghar; Bushra Shakoor; Muneerah Alomar; Muhammad Atif Ali; Yi E; Tao Mei; Muhammad Sultan Irshad; Xianbao Wang (Chemical Engineering Journal, 2025)

Photo-activated proton-incorporation into Nd-aluminum for superionic conductors - Atif Nazar; Bushra Bibi; Sajid Rauf; Rizwan Raza; Muhammad Farrukh Sarfraz; Muhammad Khalid; Muhammad Faisal Anwar; Muhammad Ahsan Masood; Kashif Nazar; Syed Asad Abbas Bukhari; Khuloud A. Alibrahim; Bin Zhu; et al. (Chemical Engineering Journal, 2025)

Bacillus Inoculation Along with Biogas Slurry Mitigates Nickel Stress in Raphanus Sativus by Regulating Ni Accumulation and the Antioxidant Defense System - Iftikhar Ahmad; Shehzad Mehmood; Muhammad Atif Muneer; Aftab Jamal; Amjad Farooq; Muhammad Farhan Saeed; Qasim Ali; Umar Daraz; Nabil Touzout; Adil Mihoub; Jun Zhou (Water, Air, & Soil Pollution, 2025)

Behavioral and systemic differences in Holstein cows with known severity of rumen acidosis during low and high-grain feeding - Rana Muhammad Atif; Patrick Biber; Thomas Hartinger; Ezequias Castillo-Lopez; Nicole Reisinger; Qendrim Zebeli (Applied Animal Behaviour Science, 2025)

Role of thiourea in wheat growth and grain yield enhancement under Cadmium-induced oxidative stress and nutrient ion diminutions - Abida Parveen; Muhammad Atif; Shagufta Perveen (Acta Physiologiae Plantarum, 2025)

Development and characterization of phosphate tailings-based humic acid slow-release fertilizer using ball milling sludge acid activation - Yinxin Xie; Qi Zhang; Deyi Yuan; Yingjie Hu; Caiyuan Guo; Muhammad Atif Muneer; Yafu Tang; Yanhui Xu; Fu Wan; Youzhi Yang (Process Safety and Environmental Protection, 2025)

An effective bi-functional electrocatalyst for electrochemical water splitting using NiCo2O4 nanoparticles decorated with Polypyrrole nanocomposite - Khadija-Tul-Kubra; Faiqa Noreen; Ali Junaid; Atif Nazir; Sehrish Arshad; Komal Bibi; Ayesha Batool; Aleeza Sattar; Aboud Ahmed Awadh Bahajjaj; Sohail Ahmad; Muhammad Shuaib Khand; Syed Imran Abbas Shah (Fuel, 2025)

Comprehensive Molecular Profiling of AcrAB-TolC Efflux Pump Genes in Salmonella typhi Isolates from Typhoid Infected Patients - Muhammad; Sadiq Azam; Noor Rehman; Alaa S. Alhegaili; Ibrar Khan; Aakash Ahmad; Atif Ali Khan Khalil; Sajid Ali (Current Microbiology, 2025)

Climate Change Impacts on Fruit Crops and Mechanisms of Stress-Induced Disease Dynamics for Resilience Strategies - Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2025)

GC–MS Profiling and Computational Analysis of Potato Peel Extracts Reveal Promising Avenue of Novel Therapeutic Potential: An Embarking Step towards Drugs Design - Iqra Sarwar; Farhat Yasmeen; Muhammad Iqbal; Muhammad Atif; Muhammad Ishaq; Zeenat Haq; Sabahat Javid; Anam Liaqat (Potato Research, 2025)

Contrasting Growth Patterns, Root Trait Plasticity, Phosphorus Uptake, and Antioxidant Responses in Maize Hybrids under Water and Phosphorus Deficiency - Hafiz Athar Hussain; Qingwen Zhang; Qurat ul Ain; Saddam Hussain; Saleem Uddin; Rubab Zahra Naqvi; Rana Muhammad Atif; Muhammad Ahmad; Asma Imran (Journal of Soil Science and Plant Nutrition, 2025)

Advancing fungal phylogenetics: integrating modern sequencing, dark taxa discovery, and machine learning - Syed Atif Hasan Naqvi; Aqleem Abbas; Ammarah Hasnain; Zeshan Bilal; Fahad Hakim; Muhammad Shabbir; Ahsan Amin; Muhammad Umer Iqbal (Archives of Microbiology, 2025)

Functionalized carbon nanotubes interconnected with metal-organic frameworks for in-situ solar-driven evaporation and salt recovery from seawater - Muhammad Sohail Asghar; Muhammad Sultan Irshad; Naila Arshad; Maryam Al Huwayz; Muneerah Alomar; Ghazala Maqsood; Muhammad Atif Ali; Uzma Ghanzanfar; Muhammad Sabir; Jinhua Li; Van-Duong Dao; Nang Xuan Ho; et al. (Water Research, 2025)

Vanadium anchored 3D nanoconfined KIT-6 silica walls for fast oxidative desulfurization of fuel: A detailed thermodynamic and kinetic examination - Afaq Nazir; Safia Gul Lalayi; Jehangir Khan; Atif Ahmad; Chen Shu Huan; Muhammad Qamer Abbas; Zhenxia Du (Journal of Hazardous Materials, 2025)

High-Sensitivity RT-LAMP Assay Enables Rapid, Field-Deployable Detection of Candidatus Liberibacter Asiaticus in Crude DNA Extracts from Citrus Phyllosphere and Psyllid Vectors - Ummad ud Din Umar; Syed Muhammad Zaka; Muhammad Nauman Tahir; Muhammad Kashif; Ateeq Ur Rehman; Sagheer Atta; Syed Atif Hasan Naqvi (Applied Fruit Science, 2025)

Comparative efficacy of imidocarb dipropionate with additive in naturally infected cattle against bovine babesiosis - Sajida Bibi; Sidra Abbas; Muhammad Arfan Zaman; Roquyya Gul; Aima Iram Batool; Iqra Khalil; Arbab Sikandar; Farhan Ahmad Atif (Veterinary Parasitology, 2025)

Mango Tree Sudden Decline disease: 65-years global perspective of ecology, biology, epidemiology, and management - Challenge of tropical landscape pathology - Syed Atif Hasan Naqvi; Muhammad Tariq Malik; Ummad Ud Din Umar; Ateeq Ur Rehman; Shakeel Ahmad; Muhammad Fahad Hakim; Ghulam Mustafa; Muhammad Farhan; Rogério Machado Pereira; Tarcísio Visintin da Silva Galdino; Marcelo Coutinho Picanço; Ricardo Siqueira da Silva (Physiological and Molecular Plant Pathology, 2025)

Scalable interlinked hierarchical porous biochar-nanosheets for efficient removal of thallium from aquatic environment - Haitao Ren; Zainab Amjad; Atif Saleem; Muhammad Usman; Kukybayeva Dina; Muhammad Haris; Junkang Guo (Journal of Hazardous Materials, 2025)

Channel morphology of the Indus, and the growing risk of floods related damages in the Indus River basin - Raveen Fatima; Salman Atif; Monique Fort; Muhammad Azmat (Natural Hazards, 2025)

Importance of an Oncology Interest Group in Medical School: Experience from a Developing Country - Hammad Atif Irshad; Abdul Rehman; Muhammad Ali Akbar Khan; Dahir Ashfaq; Munira Moosajee (Journal of Cancer Education, 2025)

Decolorization of Dye-Loaded Textile Wastewater: Elucidating the Potential of Chlorella sorokiniana Strain HIN-3 and Effect of Effluent Characteristics - Hadeeqa Arshad; Muhammad Imran; Muhammad Ashraf; Asif Naeem; Muhammad Atif Riaz (Water, Air, & Soil Pollution, 2025)

Response of Fruit Productivity, Soil Physicochemical Properties, and Microbiota to Nitrogen Reduction and Grass Cover Crops in Pomelo Orchard - Shuang Zou; Zongjun Ji; Xinhao Rao; Yingmin Guo; Muhammad Atif Muneer; Siwen Zhang; Delian Ye; Liangquan Wu; Wenhao Yang (Journal of Soil Science and Plant Nutrition, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

Taste detection of flonicamid in Drosophila melanogaster - Muhammad Atif; Youngseok Lee (Insect Biochemistry and Molecular Biology, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Amelioration of pain and adjuvant-induced arthritis by syringic acid via modulation of behavioral parameters and inflammatory mediators i.e. TNF-α, Interleukins, MCP-1, NF-kB and COX-2 - Noviara Saleem; Syed Atif Raza; Alamgeer; Muhammad Khalil-ur-Rehman; Rukhsana Anwar; Abrar Ahmed; Hafiz Muhammad Irfan (Inflammopharmacology, 2025)

Removal of structurally different textile dyes from water by adsorption onto biomass of non-viable Chlorella sorokiniana strain HIN-3: Kinetics and adsorption isotherms - Hadeeqa Arshad; Muhammad Imran; Muhammad Ashraf; Asif Naeem; Muhammad Atif Riaz (Journal of Applied Phycology, 2025)

Immunomodulatory properties of a methanolic extract of Ficus lyrata mitigate inflammation in Complete Freund’s Adjuvant-induced arthritis - Anam Iftikhar; Mohammad Saleem; Syed Atif Raza; Adrian Achuthan; Rodney Luwor; Taha Muhammad; Umair Majeed (Inflammopharmacology, 2025)

Status and prospects of omics in lentil: understanding mechanisms and impact on stress breeding under changing climate - Fawad Ali; Yiren Zhao; Arif Ali; Mian Abdur Rehman Arif; Obaid Ullah Shah; Muhammad Atif Azeem; Li Liao; Zhiyong Wang (Journal of Plant Biochemistry and Biotechnology, 2025)

Spatiotemporal pattern of climatic water balance over Balochistan, Pakistan for the period 1961–2016 - Muhammad Qasim; Kamal Ahmed; Aman Jan; Najeebullah Khan; Atif Muhammad Ali (Theoretical and Applied Climatology, 2025)

In Silico Comparison of WRKY Transcription Factors in Wild and Cultivated Soybean and Their Co-expression Network Arbitrating Disease Resistance - Muhammad Amjad Nawaz; Hafiz Kashif Khalil; Farrukh Azeem; Muhammad Amjad Ali; Igor Eduardovich Pamirsky; Kirill S. Golokhvast; Seung Hwan Yang; Rana Muhammad Atif; Gyuhwa Chung (Biochemical Genetics, 2025)

Fungicide resistance in Fusarium species: exploring environmental impacts and sustainable management strategies - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Muhammad Shahbaz; Aqleem Abbas; Fahad Hakim; Muhammad Shabbir; Yee Shin Tan; Jaya Seelan Sathiya Seelan (Archives of Microbiology, 2025)

Microwave-assisted, sulfhydryl-modified β-cyclodextrin-silymarin inclusion complex: A diverse approach to improve oral drug bioavailability via enhanced mucoadhesion and permeation - Shumaila Arshad; Syed Atif Raza; Alamgeer; Syed Nasir Abbas Bukhari; Nasser F. Alotaibi; Naveed Ahmad; Hafiz Muhammad Irfan; Arshad Mahmood; Mulazim Hussain Asim (Carbohydrate Polymers, 2025)

Effect of Arsenic Exposure on AS3MT Protein Levels in Serum of Type 2 Diabetic Patients Compared to Non-diabetics - Saima Shokat; Riffat Iqbal; Muhammad Ahmed Ali; Atif Yaqub; Shaista Aslam; Samreen Riaz (Biological Trace Element Research, 2024)

Potential of iron oxide-modified biochar in simultaneous mitigation of lead and nickel toxicity in wheat (Triticum aestivum L.) - Tufail Shah; Muhammad Kashif Irshad; Wasim Javed; Mahshab Sheraz; Atif Muhmood; Ali Noman; Maryam M. Alomran; Sang Soo Lee; Jianying Shang (South African Journal of Botany, 2024)

Calcium oxide nanoparticles ameliorate cadmium toxicity in alfalfa seedlings by depriving its bioaccumulation, enhancing photosystem II functionality and antioxidant gene expression - Maqsood Ul Hussan; Sadam Hussain; Muhammad Adeel; Atif Ayub; Hafiz Abdul Kareem; Shaista Jabeen; Muhammad Saqib; Quanzhen Wang; Mingke Yan; Kadambot H.M. Siddique; Muhammad Tahir (Science of The Total Environment, 2024)

Investigating the potential of 1,2,4-triazoles as corrosion inhibitors for copper and steel: A comprehensive review - Aqsa Ashraf; Naheed Riaz; Saima Muzaffar; Muhammad Atif; Bushra Bashir (Next Research, 2024)

Harmonizing traditional and biotechnological approaches to engineer crop microbiomes: Enhancing resilience optimization - Muhammad Siddique Afridi; Abdul salam; Sher Ali; Sumaira; Willian César Terra; Baber Ali; Muhammad Atif Muneer; Gustavo Santoyo (Biocatalysis and Agricultural Biotechnology, 2024)

Association of polymorphism of NLRP3, ICAM-1, PTPN22, INS genes in childhood onset type 1 diabetes in a Pakistani population - Anjum Jabeen; Samreen Riaz; Muhammad Usman; Asia Parveen; Maryam Mukhtar; Abdul Wajid; Atif Hanif; Andleeb Batool (Molecular Biology Reports, 2024)

Adenosine A2AR in viral immune evasion and therapy: unveiling new avenues for treating COVID-19 and AIDS - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Sajjad Ullah; Abualgasim Elgaili Abdalla; Muhammad Ikram Ullah; Bi Bi Zainab Mazhari; Lienda Bashier Eltayeb; Ismail Hamad; Hasan Ejaz (Molecular Biology Reports, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Conjoint effect of indole-3-acetic acid and vitamin B1 on nutrient acquisition and seed oil physicochemical properties of Zea mays L. under arsenic intervention - Muhammad Atif; Shagufta Perveen; Abida Parveen; Farah Saeed (Journal of Plant Growth Regulation, 2024)

Elucidating the protective role of manganese seed priming in mitigating lead-induced oxidative stress: enhancements in growth, grain yield, and antioxidant activities of wheat - Abida Parveen; Muhammad Atif; Faiza Akhtar; Shagufta Perveen; Sara Zafar; Khadija Hafeez; Nadia Yasmeen (Environmental Science and Pollution Research, 2024)

Role of pressmud compost for reducing toxic metals availability and improving plant growth in polluted soil: Challenges and recommendations - Altaf Hussain Lahori; Maira Tunio; Samreen Riaz Ahmed; Monika Mierzwa-Hersztek; Viola Vambol; Ambreen Afzal; Anila Kausar; Sergij Vambol; Aqsa Umar; Atif Muhammad (Science of The Total Environment, 2024)

Handwashing basins and healthcare associated infections: Bacterial diversity in biofilms on faucets and drains - Claire Hayward; Kirstin E. Ross; Melissa H. Brown; Muhammad Atif Nisar; Jason Hinds; Tamar Jamieson; Sophie C. Leterme; Harriet Whiley (Science of The Total Environment, 2024)

Wet ball milling activated oyster shells for multifunctional slow-release compound fertilizer production - Weiqiang Zhang; Dian jin; Caixia Liu; Muhammad Atif Muneer; Huanhuan Zhu; Taoyu Ren; Hongnan Xu; Jingwen Wang; Zhenya Lu; Deyi Yuan; Yafu Tang (Chemical Engineering Journal, 2024)

Deciphering fungicide resistance in Phytophthora: mechanisms, prevalence, and sustainable management approaches - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (World Journal of Microbiology and Biotechnology, 2024)

Spatio-temporal remote sensing evaluation of drought impact on vegetation dynamics in Balochistan, Pakistan - Atif Muhammad Ali; Haishen Lü; Yonghua Zhu; Kamal Ahmed; Muhammad Farhan; Muhammad Qasim (Theoretical and Applied Climatology, 2024)

Exogenous Application of Silicon and Zinc Attenuates Drought Tolerance in Eruca sativa L. Through Increasing Chlorophyll Pigments, Osmoprotectants, and Modulating Defense Mechanisms - Iqbal Hussain; Atif Ayub; Airish Nayab; Muhammad Arslan Ashraf; Muhammad Arslan Ashraf; Sadam Hussain; Manzer H. Siddiqui; Muhammad Azeem Sabir; Usman Zulfiqar; Tanveer Hussain Khan (Journal of Plant Growth Regulation, 2024)

Retraction Note: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Characterization of two novel fusariviruses co-infecting a single isolate of phytopathogenic fungus Botrytis cinerea - Aqeel Ahmed; Haris Ahmed Khan; Atif Jamal; Nasar Virk; Muhammad Faraz Bhatti (Virus Genes, 2024)

Optimizing Micronutrient Supplementation in Mango Orchards for the Suppression of Mango Anthracnose (Colletotrichum gloeosporioides) - Wajid Nazir; Syed Atif Hasan Naqvi; Niaz Ahmed; Ateeq ur Rehman; Abdulwahed Fahad Alrefaei; Muhammad Asif Zulfiqar; Ummad ud Din Umar (Applied Fruit Science, 2024)

Retraction Note: Unlocking the role of energy poverty and its impacts on financial growth of household: is there any economic concern - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Hieu Minh Vu; Muhammad Atif Nawaz (Environmental Science and Pollution Research, 2024)

Facilitated transport of ferrihydrite with phosphate under saturated flow conditions - Tufail Shah; Kang Zhao; Ai Chen; Atif Muhmood; Syed Atizaz Ali Shah; Muhammad Kashif Irshad; Yuji Arai; Jianying Shang (Journal of Contaminant Hydrology, 2024)

Extremophiles and their enzymatic diversity and biotechnological potential - Fatima Atif; Nida Maqsood; Wajeeha Ali; Wajid Ali; Muhammad Irfan (Systems Microbiology and Biomanufacturing, 2024)

Hybrid constructed wetlands and filamentous fungi for treatment of mixed sewage and industrial effluents - Atif Mustafa; Muhammad Kamran Azim; Qandeel Laraib; Qazi Muneeb Ur Rehman (Environmental Science and Pollution Research, 2024)

Inhibitory potential of Syzygium aromaticum against Fusarium oxysporum f. sp. lycopersici: In-vitro analysis and molecular docking studies - Muhammad Atif; Tehmina Anjum; Ahmad Ali Shahid; Ahmad Hassan; Waheed Akram (South African Journal of Botany, 2024)

Establishing quality evaluation standards for pomelo fruit: The role of harvesting time and appearance characteristic - Xiaojun Yan; Muhammad Atif Muneer; Mengting Qin; Jie Ou; Xiaohui Chen; Zhiyuan He; Yedong Liu; Zhihan Cheng; Da Su; Rongrong Liu; Liangquan Wu (Postharvest Biology and Technology, 2024)

Genomic insights into local adaptation of upland cotton in China and Pakistan - Zegang Han; Zhanfeng Si; Mehboob-ur Rahman; Lu He; Yiqian Li; Ali Qaiser Khan; Yun Mao; Sana Zulfiqar; Shumila Ishfaq; Muhammad Mohsan; Muhammad Atif Iqbal; Saba Zafar; et al. (Theoretical and Applied Genetics, 2024)

Unraveling the contribution of copper seed priming in enhancing chromium tolerance in wheat by improving germination, growth, and grain yield - Khadija Hafeez; Muhammad Atif; Shagufta Perveen; Abida Parveen; Faiza Akhtar; Nadia Yasmeen (Environmental Science and Pollution Research, 2024)

Optimal environment control and fruits delivery tracking system using blockchain for greenhouse - Atif Rizwan; Anam Nawaz Khan; Muhammad Ibrahim; Rashid Ahmad; Naeem Iqbal; Do Hyeun Kim (Computers and Electronics in Agriculture, 2024)

Appraisal of the health hazards associated with the ingestion of vegetables contaminated with potentially toxic elements - Ali Afzal; Atif Muhmood; Syed Ayyaz Javed; Arslan Nazarat; Muhammad Rashid; Asrar Hussain Shah; Farhana Siddique (Arabian Journal of Geosciences, 2024)

Unveiling Intricacies of Mango Malformation Dynamics Caused by Fusarium solani Through Extensive Field Surveys and Laboratory, Epidemiology, and Model-Based Insights - Abdurrehman; Talha Mansoor; Muhammad Nasir Subhani; Muhammad Tariq Malik; Ammarah Hasnain; Aqleem Abbas; Abdulwahed Fahad Alrefaei; Haider Ali; Muhammad Zeeshan Hassan; Syed Atif Hasan Naqvi (Applied Fruit Science, 2024)

Optimization of multi-stage micellar-enhanced flocculation process for removal of Levofloxacin hemihydrate in wastewater - Fiza Bukhtawar; Muhammad Usman; Atta Ul Haq; Muhammad Saeed; Atif Saleem (Journal of Water Process Engineering, 2024)

Compositional shifts in rhizobacterial communities of Brassica napus under salinity stress - Muhammad Laiq; Muhammad Atif Azeem; Sara Begum; Nausheen Nazir; Zakia Ahmad; Sana Ullah; Mohammad Nisar; Abid Ullah (Applied Soil Ecology, 2024)

Protective role of manganese, proline and rice straw extract in wheat against drought driven oxidative stress - Abida Parveen; Shagufta Perveen; Sana Tariq; Muhammad Atif; Farah Saeed; Sara Zafar (Acta Physiologiae Plantarum, 2024)

Mitigating life-cycle environmental impacts and increasing net ecosystem economic benefits via optimized fertilization combined with lime in pomelo production in Southeast China - Xiaojun Yan; Yifei Ma; Kunpeng Kong; Muhammad Atif Muneer; Lijun Zhang; Yadong Zhang; Zhihan Cheng; Ziwei Luo; Changcheng Ma; Chaoyuan Zheng; Wenhao Yang; Jiuxin Guo; et al. (Science of The Total Environment, 2024)

Corrigendum to “Evaluation of nanoceria on cadmium uptake in Triticum aestivum (L.) and its implications for dietary health risk” [Chemosphere 341 November (2023) 140115] - Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Zahid Khorshid Abbas; Nora M. Al Aboud; Nasir Masood; Muhammad Atif Irshad; Tahir Abbas; Amany H.A. Abeed; Doaa Bahaa Eldin Darwish (Chemosphere, 2024)

Role of fintech, green finance, and natural resource rents in sustainable climate change in China. Mediating role of environmental regulations and government interventions in the pre-post COVID eras - Muhammad Sadiq; Ch Paramaiah; Robinson joseph; Ziguang Dong; Muhammad Atif Nawaz; Nizomjon Khajimuratov Shukurullaevich (Resources Policy, 2024)

CRISPR/Cas9-based genome editing: A revolutionary approach for crop improvement and global food security - Ghulam Muha-Ud-Din; Faizan Ali; Akhtar Hameed; Syed Atif Hasan Naqvi; Mir Muhammad Nizamani; Muhammad Jabran; Sohaib Sarfraz; Wang Yong (Physiological and Molecular Plant Pathology, 2024)

Assessing coastal bathymetry and climate change impacts on coastal ecosystems using Landsat 8 and Sentinel-2 satellite imagery - Kasypi Mokhtar; Lai Fatt Chuah; Mohd Azhafiz Abdullah; Olakunle Oloruntobi; Siti Marsila Mhd Ruslan; Gadah Albasher; Atif Ali; Muhammad Saeed Akhtar (Environmental Research, 2023)

Enhancing coastal ecosystem resilience: Investigating the interplay between safety criteria and ferry employee's perceptions to address climate change impacts - Muhammad Azizol Azmi; Kasypi Mokhtar; Noor Apandi Osnin; Suzanna Razali Chan; Gadah Albasher; Atif Ali; Alam Nawaz; Olakunle Oloruntobi; Lai Fatt Chuah (Environmental Research, 2023)

Intervening Role of Tyrosine in Cadmium Detoxification, Balancing of Mineral Ions Homeostasis, Antioxidants, and Secondary Metabolites in Maize - Muhammad Atif; Shagufta Perveen; Abida Parveen; Sara Zafar; Fatima Batool; Farah Saeed (Journal of Soil Science and Plant Nutrition, 2023)

Unlocking the secrets of soil microbes: How decades-long contamination and heavy metals accumulation from sewage water and industrial effluents shape soil biological health - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Niaz Ahmed; Sajjad Hussain; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Javeed Shabbir Dar; Mahmoud Moustafa; Mohammed O. Alshaharni (Chemosphere, 2023)

Evaluation of nanoceria on cadmium uptake in Triticum aestivum (L.) and its implications for dietary health risk - Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Zahid Khorshid Abbas; Nora M. Al Aboud; Nasir Masood; Muhammad Atif Irshad; Tahir Abbas; Amany H.A. Abeed; Doaa Bahaa Eldin Darwish (Chemosphere, 2023)

Synergistic effect of β-sitosterol and biochar application for improving plant growth of Thymus vulgaris under heat stress - Khadiga Alharbi; Amir Abdullah Khan; Haifa Abdulaziz Sakit Alhaithloul; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Saeedah Sallum Aloufi; Awatif M. Abdulmajeed; Muhammad Atif Muneer; Suliman M.S. Alghanem; Muhammad Zia-ur-Rehman; Muhammad Usman; Mona H. Soliman (Chemosphere, 2023)

Risk assessment of toxic and hazardous metals in paddy agroecosystem by biochar-for bio-membrane applications - Muhammad Kashif Irshad; Sihang Zhu; Wasim Javed; Jong Cheol Lee; Abid Mahmood; Sang Soo Lee; Shang Jianying; Gadah Albasher; Atif Ali (Chemosphere, 2023)

Linking tourist's footprint and environmental tragedy through transportation, globalization and energy choice in BIMSTEC region: Directions for a sustainable solution using novel GMM-PVAR approach - Atif Jahanger; Mohammad Razib Hossain; Ashar Awan; Tomiwa Sunday Adebayo; Muhammad Zubair Chishti (Journal of Environmental Management, 2023)

Effects of soil amendments on soil acidity and crop yields in acidic soils: A world-wide meta-analysis - Siwen Zhang; Qichao Zhu; Wim de Vries; Gerard H. Ros; Xiaohui Chen; Muhammad Atif Muneer; Fusuo Zhang; Liangquang Wu (Journal of Environmental Management, 2023)

Role of gibberellins, neem leaf extract, and serine in improving wheat growth and grain yield under drought-triggered oxidative stress - Sidra Hameed; Muhammad Atif; Shagufta Perveen (Physiology and Molecular Biology of Plants, 2023)

Inconsistent responses of soil bacterial and fungal community's diversity and network to magnesium fertilization in tea (Camellia sinensis) plantation soils - Wenhao Yang; Zongjun Ji; Aolin Wu; Dongdong He; Christopher Rensing; Yanhua Chen; Chengcong Chen; Huihuang Wu; Muhammad Atif Muneer; Liangquan Wu (Applied Soil Ecology, 2023)

Green synthesis and characterization of silver and copper nanoparticles and their use as an effective adsorbent for chromium removal and recovery from wastewater - Muhammad Atif Irshad; Sana Sattar; Arwa Abdulkreem AL-Huqail; Suliman M. S. Alghanem; Rab Nawaz; Noor ul Ain; Khalid Mahmud Hussaini; Amany H. A. Abeed (Environmental Science and Pollution Research, 2023)

Effect of green synthesized cerium oxide nanoparticles on fungal disease of wheat plants: A field study - Modhi O. Alotaibi; Nahaa M. Alotaibi; Adel M. Ghoneim; Noor ul Ain; Muhammad Atif Irshad; Rab Nawaz; Tahir Abbas; Amjad Abbas; Muhammad Rizwan; Shafaqat Ali (Chemosphere, 2023)

Cotton and drought stress: An updated overview for improving stress tolerance - Sadia Zafar; Hadiqa Afzal; Areeba Ijaz; Athar Mahmood; Atif Ayub; Airish Nayab; Sadam Hussain; Maqsood UL-Hussan; Muhammad Azeem Sabir; Usman Zulfiqar; Faisal Zulfiqar; Anam Moosa (South African Journal of Botany, 2023)

Implications for optimal abatement path through the deployment of natural resources, human development, and energy consumption in the era of digitalization - Atif Jahanger; Muhammad Usman; Rakhshanda Kousar; Daniel Balsalobre-Lorente (Resources Policy, 2023)

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Immunomodulation, Fish Health and Resistance to Staphylococcus aureus of Nile Tilapia (Oreochromis niloticus) Fed Diet Supplemented with Zinc Oxide Nanoparticles and Zinc Acetate - Atif Yaqub; Muhammad Nasir; Muhammad Kamran; Iqra Majeed; Aneeza Arif (Biological Trace Element Research, 2023)

The effect of gibberellic acid on wheat growth and nutrient uptake under combined stress of cerium, zinc and titanium dioxide nanoparticles - Arwa Abdulkreem AL-Huqail; Dikhnah Alshehri; Rab Nawaz; Muhammad Atif Irshad; Azka Iftikhar; Khalid Mahmud Hussaini; Muhammad Rizwan; Suliman M.S. Alghanem; Amany H.A. Abeed (Chemosphere, 2023)

Preparation and characterization of single perovskite microplates and its sunlight assisted photodecolorization activity, validated by response surface methodology - Arif Nawaz; Irum Naz; Muhammad Atif; Adnan Khan; Nisar Ali (Chemosphere, 2023)

The composition of planktonic prokaryotic communities in a hospital building water system depends on both incoming water and flow dynamics - Muhammad Atif Nisar; Kirstin E Ross; Melissa H Brown; Richard Bentham; James Xi; Jason Hinds; Tamar Jamieson; Sophie C Leterme; Harriet Whiley (Water Research, 2023)

The presence of mycoviral infection attenuates the growth and pathogenicity of the phytopathogenic fungus Botrytis cinerea collected from strawberry fields in Pakistan - Aqeel Ahmed; Haris Ahmed Khan; Atif Jamal; Danish Ilyas Baig; Tehsin Fatma; Nasar Virk; Muhammad Faraz Bhatti (European Journal of Plant Pathology, 2023)

Dynamic linkages between globalization, human capital, and carbon dioxide emissions: empirical evidence from developing economies - Atif Jahanger; Bo Yang; Wei-Chiao Huang; Muntasir Murshed; Muhammad Usman; Magdalena Radulescu (Environment, Development and Sustainability, 2023)

Transcriptomic analysis of Cucumis sativus uncovers putative genes related to hormone signaling under low temperature (LT) and high humidity (HH) stress - Bakht Amin; Muhammad Jawaad Atif; Yupeng Pan; Shabir A. Rather; Muhammad Ali; Shuju Li; Zhihui Cheng (Plant Science, 2023)

Effect of titanium dioxide nanoparticles and co-composted biochar on growth and Cd uptake by wheat plants: A field study - Fu Chen; Yuhang Li; Muhammad Atif Irshad; Afzal Hussain; Rab Nawaz; Muhammad Farooq Qayyum; Jing Ma; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Shafaqat Ali (Environmental Research, 2023)

Solar light driven degradation of textile dye contaminants for wastewater treatment – studies of novel polycationic selenide photocatalyst and process optimization by response surface methodology desirability factor - Arif Nawaz; Muhammad Atif; Adnan Khan; Mohsin Siddique; Nisar Ali; Falak Naz; Muhammad Bilal; Tak H. Kim; Malwina Momotko; Hameed Ul Haq; Grzegorz Boczkaj (Chemosphere, 2023)

“Retraction notice to Carveol ameliorates mercury-induced oxidative stress, neuroinflammation, and neurodegeneration in a mouse brain” NeuroToxicology 92 (2022) 212–226 - Abdullah Alattar; Arooj Mohsin Alvi; Sajid Rashid; Nadia Hussain; Mehreen Gul; Muhammad Ikram; Atif Ali Khan Khalil; Reem Alshaman; Fawad Ali Shah; Shupeng Li; Jingbo Li (NeuroToxicology, 2023)

Co-opted directors and greenhouse gas emissions: Does ESG compensation matter? - Ammar Ali Gull; Aitzaz Ahsan Alias Sarang; Irfan Haider Shakri; Muhammad Atif (Journal of Cleaner Production, 2023)

Synthesis, characterization and antifungal potential of titanium dioxide nanoparticles against fungal disease (Ustilago tritici) of wheat (Triticum aestivum L.) - Nadiyah M. Alabdallah; Muhammad Atif Irshad; Muhammad Rizwan; Rab Nawaz; Aqil Inam; Muhammad Mohsin; Iram Khurshid; Hesham F. Alharby; Atif A. Bamagoos; Shafaqat Ali (Environmental Research, 2023)

Exogenous application of low and high molecular weight organic acids differentially affected the uptake of cadmium in wheat-rice cropping system in alkaline calcareous soil - Muhammad Zia-ur-Rehman; Manar Fawzi Bani Mfarrej; Muhammad Usman; Muhammad Azhar; Muhammad Rizwan; Hesham F. Alharby; Atif A. Bamagoos; Rahma Alshamrani; Zahoor Ahmad (Environmental Pollution, 2023)

Reduction in the cadmium (Cd) accumulation and toxicity in pearl millet (Pennisetum glaucum L.) by regulating physio-biochemical and antioxidant defense system via soil and foliar application of melatonin - Samrah Afzal Awan; Imran Khan; Muhammad Rizwan; Muhammad Atif Irshad; Wang Xiaosan; Xinquan Zhang; Linkai Huang (Environmental Pollution, 2023)

The role of fiscal decentralization and technological innovations in curbing sulfur dioxide emissions: formulating SDGs policies for China - Ayoub Zeraibi; Atif Jahanger; Muhammad Usman; Daniel Balsalobre-Lorente; Tomiwa Sunday Adebayo; Mustafa Kamal (Environment, Development and Sustainability, 2023)

Differential response of nano zinc sulphate with other conventional sources of Zn in mitigating salinity stress in rice grown on saline-sodic soil - Rubaz Ahmed; Muhammad Zia-ur-Rehman; Muhammad Sabir; Muhammad Usman; Muhammad Rizwan; Zahoor Ahmad; Hesham F. Alharby; Hassan S. Al-Zahrani; Hameed Alsamadany; Amal Y. Aldhebiani; Yahya M. Alzahrani; Atif A. Bamagoos (Chemosphere, 2023)

Effects of silicon nanoparticles and conventional Si amendments on growth and nutrient accumulation by maize (Zea mays L.) grown in saline-sodic soil - Ali Rizwan; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Muhammad Usman; Sidra Anayatullah; Areej; Hesham F. Alharby; Atif A. Bamagoos; Basmah M. Alharbi; Shafaqat Ali (Environmental Research, 2023)

Exploration of plant growth promoting traits and regulatory mechanisms of Bacillus anthracis PM21 in enhancing salt stress tolerance in maize - Muhammad Atif Azeem; Fawad Ali; Abid Ullah; Mahmood Iqbal; Kishwar Ali; Dunia A. Al Farraj; Mohamed S. Elshikh; Qirat Naz; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2023)

A review on covalent organic frameworks as adsorbents for organic pollutants - Awais Ali Aslam; Adnan Irshad; Muhammad Shahid Nazir; Muhammad Atif (Journal of Cleaner Production, 2023)

Greenfield investments, economic complexity, and financial inclusion-environmental quality nexus in BRICS Countries: Does renewable energy transition matter? - Ayoub Zeraibi; Atif Jahanger; Tomiwa Sunday Adebayo; Muhammad Ramzan; Yang Yu (Gondwana Research, 2023)

Determinants of environmental quality in India: evidence using the bootstrapped ARDL model with structural breaks - Samiha Khan; Rafael Alvarado; Muhammad Atif Nawaz; Zahoor Ahmed; Abdul Rehman; Syed Margub Elahi (Environmental Science and Pollution Research, 2023)

Vegetable oils as bio-based precursors for epoxies - Fareeha Marriam; Adnan Irshad; Isra Umer; Muhammad Arslan Asghar; Muhammad Atif (Sustainable Chemistry and Pharmacy, 2023)

Plant community and soil available nutrients drive arbuscular mycorrhizal fungal community shifts during alpine meadow degradation - Keyu Chen; Jing Zhang; Muhammad Atif Muneer; Kai Xue; Haishan Niu; Baoming Ji (Fungal Ecology, 2023)

RETRACTED ARTICLE: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Discrimination of lithofacies in tight gas reservoir using field-specific rock physics modeling scheme. A case study from a mature field of middle Indus Basin, Pakistan - Muhammad Zahid Afzal Durrani; Syed Atif Rahman; Maryam Talib; Bakhtawer Sarosh (Acta Geophysica, 2023)

Effect of environmental taxes on environmental innovation and carbon intensity in China: an empirical investigation - Qian Zhang; Saba Anwer; Muhammad Hafeez; Atif Khan Jadoon; Zahoor Ahmed (Environmental Science and Pollution Research, 2023)

Recent scenario and nexus between natural resource dependence, energy use and pollution cycles in BRICS region: Does the mediating role of human capital exist? - Atif Jahanger; Mohammad Razib Hossain; Muhammad Usman; Joshua Chukwuma Onwe (Resources Policy, 2023)

Detection and quantification of aflatoxins in spices stored in different food packaging materials - Muhammad Abrar; Samreen Ahsan; Muhmmad Nadeem; Atif Liaqat; Muhmmad Farhan Jahangir Chughtai; Muhammad Adil Farooq; Tariq Mehmood; Adnan Khaliq; Ayesha Siddiqa (Journal of Stored Products Research, 2023)

Bombax ceiba flower extract mediated synthesis of Se nanoparticles for antibacterial activity and urea detection - Muhammad Safdar; Sidra Aslam; Misbah Akram; Adnan Khaliq; Samreen Ahsan; Atif Liaqat; Misbah Mirza; Muhammad Waqas; Waseem Akhtar Qureshi (World Journal of Microbiology and Biotechnology, 2023)

Experimental Characterization-Based Machine Learning Modeling for the Estimation of Geotechnical Properties of Clay Liners - Hafiz Muhammad Awais Rashid; Muhammad Sufyan; Atif Ismail; Umer Waqas (Geotechnical and Geological Engineering, 2023)

Maize grain nutritional quality amelioration with seed-applied thiamine and indole-3-acetic acid under arsenic toxicity - Muhammad Atif; Shagufta Perveen (Environment, Development and Sustainability, 2023)

Effect of farmyard manure, elemental sulphur and EDTA on growth and phytoextraction of cadmium by spider plants (Chlorophytum comosum L.) under Cd stress - Muhammad Zia-ur-Rehman; Arisha Mubsher; Muhammad Rizwan; Muhammad Usman; Muhammad Jafir; Muhammad Umair; Hesham F. Alharby; Atif A. Bamagoos; Rahma Alshamrani; Shafaqat Ali (Chemosphere, 2023)

Achieving business competitiveness through corporate social responsibility and dynamic capabilities: An empirical evidence from emerging economy - Huma Sarwar; Junaid Aftab; Muhammad Ishtiaq Ishaq; Muhammad Atif (Journal of Cleaner Production, 2023)

The relevance of international tourism and natural resource rents in economic growth: Fresh evidence from MINT countries in the digital era - Daniel Balsalobre-Lorente; Lucia Ibañez Luzon; Muhammad Usman; Atif Jahanger (Environmental Science and Pollution Research, 2023)

Are Mercosur economies going green or going away? An empirical investigation of the association between technological innovations, energy use, natural resources and GHG emissions - Muhammad Usman; Daniel Balsalobre-Lorente; Atif Jahanger; Paiman Ahmad (Gondwana Research, 2023)

Application of Nanomaterials for Cadmium Adsorption for Sustainable Treatment of Wastewater: a Review - Muhammad Atif Irshad; Rab Nawaz; Ewa Wojciechowska; Muhammad Mohsin; Nicole Nawrot; Iqra Nasim; Fida Hussain (Water, Air, & Soil Pollution, 2023)

Biochemical and Physiological Responses of Cucumis sativus Cultivars to Different Combinations of Low-Temperature and High Humidity - Bakht Amin; Muhammad Jawaad Atif; Huanwen Meng; Muhammad Imran Ghani; Muhammad Ali; Xiao Wang; Yuanyuan Ding; Xiuju Li; Zhihui Cheng (Journal of Plant Growth Regulation, 2023)

Microplastics in water, sediments, and fish at Alpine River, originating from the Hindu Kush Mountain, Pakistan: implications for conservation - Muhammad Bilal; Abdul Qadir; Atif Yaqub; Habib Ul Hassan; Muhammad Irfan; Mehmood Aslam (Environmental Science and Pollution Research, 2023)

Sedimentology and diagenesis control on reservoir quality of Sheikhan Limestone (Eocene) at the Panoba and Sheikhan Nala Section, Kohat Basin, Pakistan - Atif Salim; Muhammad Kashif; Bin Dou; Danish Khan; Muhammad Jawad Munawar; Noor Ahmed; Naveed Rehman; Muhammad Sajid; Zahid Ullah; Muhammad Tariq (Carbonates and Evaporites, 2022)

A quantitative assessment of pollution from potentially toxic elements in groundwater and the accompanying health risks - Atif Muhmood; Abdul Majeed; Abid Niaz; Asrar Hussain Shah; Ali Afzal; Khaliq ur Rehman Arshad; Muhammad Rashid; Arslan Nazarat (Arabian Journal of Geosciences, 2022)

Dirty versus clean fuel for cooking in Pakistan: regional mapping and correlates - Tusawar Iftikhar Ahmad; Muhammad Atif Nawaz; Kokab Kiran; Vishal Dagar; Muhammad Azhar Bhatti; Altaf Hussain (Environmental Science and Pollution Research, 2022)

Diversified crop rotation improves continuous monocropping eggplant production by altering the soil microbial community and biochemical properties - Muhammad Imran Ghani; Ahmad Ali; Muhammad Jawaad Atif; Shamina Imran Pathan; Giacomo Pietramellara; Muhammad Ali; Bakht Amin; Zhihui Cheng (Plant and Soil, 2022)

Adenosine A2A receptor as a potential target for improving cancer immunotherapy - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Muhammad Ikram Ullah; Ayman Ali Mohammed Alameen; Muhammad Imran; Hasan Ejaz (Molecular Biology Reports, 2022)

A novel lens of stock market capitalization and environmental degradation - Aamir Azeem; Muhammad Akram Naseem; Naveed Ul Hassan; Ijaz Butt; Muhammad Toseef Aslam; Shahid Ali; Atif khan Jadoon (Environmental Science and Pollution Research, 2022)

Testing stationarity of per capita energy consumption across the globe: a better picture using the wavelet framework - Mumtaz Ahmed; Muhammad Azam; Atif Maqbool Khan (Environmental Science and Pollution Research, 2022)

Exploring the asymmetric determinants of consumption and production-based CO2 emissions in China - Muhammad Hafeez; Juan Yang; Atif Khan Jadoon; Israt Zahan; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2022)

Quantitative characterization of unconventional (tight) hydrocarbon reservoir by integrating rock physics analysis and seismic inversion: a case study from the Lower Indus Basin of Pakistan - Maryam Talib; Muhammad Zahid Afzal Durrani; Arshad Hussain Palekar; Bakhtawer Sarosh; Syed Atif Rahman (Acta Geophysica, 2022)

Development of Optimized Sumatriptan–Prochlorperazine Combined Orodispersible Films Without Disintegrant: in vitro, ex vivo and in vivo Characterization - Sana Javed; Amjad Hussain; Pervaiz Akhtar Shah; Syed Atif Raza; Ubaid Ullah Anwer; Rahat Shamim; Fatima Rasool; Muhammad Ahsan Hafiz; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2022)

RETRACTED ARTICLE: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2022)

Impact of coal rents, transportation, electricity consumption, and economic globalization on ecological footprint in the USA - Zheng Wenlong; Muhammad Atif Nawaz; Amena Sibghatullah; Syed Ehsan Ullah; Supat Chupradit; Vu Minh Hieu (Environmental Science and Pollution Research, 2022)

First report on molecular surveillance based on duplex detection of Anaplasma marginale and Theileria annulata in dairy cattle from Punjab, Pakistan - Farhan Ahmad Atif; Rao Zahid Abbas; Saba Mehnaz; Muhmmad Fiaz Qamar; Kashif Hussain; Muhammad Usman Nazir; Muhammad Arfan Zaman; Aman Ullah Khan; Mourad Ben Said (Tropical Animal Health and Production, 2022)

Determinants of renewable energy sources in Pakistan: An overview - Umar Suffian Ahmad; Muhammad Usman; Saddam Hussain; Atif Jahanger; Maira Abrar (Environmental Science and Pollution Research, 2022)

A novel victorivirus from the phytopathogenic fungus Neofusicoccum parvum - Haris Ahmed Khan; Yukiyo Sato; Hideki Kondo; Atif Jamal; Muhammad Faraz Bhatti; Nobuhiro Suzuki (Archives of Virology, 2022)

RETRACTED ARTICLE: Unlocking the role of energy poverty and its impacts on financial growth of household: is there any economic concern - Fengsheng Chien; Ching-Chi Hsu; YunQian Zhang; Hieu Minh Vu; Muhammad Atif Nawaz (Environmental Science and Pollution Research, 2022)

A step towards sustainable path: The effect of globalization on China’s carbon productivity from panel threshold approach - Atif Jahanger; Muhammad Usman; Paiman Ahmad (Environmental Science and Pollution Research, 2022)

Assessing the prioritization of barriers toward green innovation: small and medium enterprises Nexus - Fengsheng Chien; Hafiz Waqas Kamran; Muhammad Atif Nawaz; Nguyen Ngoc Thach; Pham Dinh Long; Zulfiqar Ali Baloch (Environment, Development and Sustainability, 2022)

A multi-perspective assessment approach of renewable energy production: policy perspective analysis - Zulfiqar Ali Baloch; Qingmei Tan; Hafiz Waqas Kamran; Muhammad Atif Nawaz; Gadah Albashar; Javaria Hameed (Environment, Development and Sustainability, 2022)

Response of dry matter partition and yield components to waterlogging and sunlight shortage in different growth stages of wheat - Min Jiang; Shouli Xuan; Muhammad Atif Muneer; Bin Sun; Chunlin Shi; Fengshan Liu; Renye Wu (Natural Hazards, 2022)

Comparative efficacy of different biochars and traditional manures in the attenuation of cadmium toxicity in rice (Oryza sativa L.) - Abdul Majeed; Atif Muhmood; Abid Niaz; Allah Ditta; Muhammad Nawaz Rajpar (Arabian Journal of Geosciences, 2022)

Genome-wide identification and characterization of a plant-specific Dof transcription factor gene family in olive (Olea europaea) and its comparison with Arabidopsis - Mariyam; Muhammad Shafiq; Muhammad Haseeb; Rana Muhammad Atif; Syed Agha Armaghan Asad Abbas Naqvi; Numan Ali; Muhammad Arshad Javed; Fizza Gillani; Muhammad Saleem Haider (Horticulture, Environment, and Biotechnology, 2021)

Physical mapping of QTL associated with agronomic and end-use quality traits in spring wheat under conventional and organic management systems - Kassa Semagn; Muhammad Iqbal; Hua Chen; Enid Perez-Lara; Darcy H. Bemister; Rongrong Xiang; Jun Zou; Muhammad Asif; Atif Kamran; Amidou N’Diaye; Harpinder Randhawa; Brian L. Beres; et al. (Theoretical and Applied Genetics, 2021)

Historical trends in crop water demand over semiarid region of Syria - Rajab Homsi; Shamsuddin Shahid; Zafar Iqbal; Atif Muhammad Ali; Ghaith Falah Ziarh (Theoretical and Applied Climatology, 2021)

A second capsidless hadakavirus strain with 10 positive-sense single-stranded RNA genomic segments from Fusarium nygamai - Haris Ahmed Khan; Yukiyo Sato; Hideki Kondo; Atif Jamal; Muhammad Faraz Bhatti; Nobuhiro Suzuki (Archives of Virology, 2021)

Deciphering distinct biological control and growth promoting potential of multi-stress tolerant Bacillus subtilis PM32 for potato stem canker - Shehzad Mehmood; Muhammad Atif Muneer; Muhammad Tahir; Muhammad Tariq Javed; Tariq Mahmood; Muhammad Siddique Afridi; Najeeba Paree Pakar; Hina Ali Abbasi; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2021)

Investigating the flood damages in Lower Indus Basin since 2000: Spatiotemporal analyses of the major flood events - Salman Atif; Muhammad Umar; Fahim Ullah (Natural Hazards, 2021)

Efficacy of rhizobacterial exopolysaccharides in improving plant growth, physiology, and soil properties - Abubakar Dar; Zahir Ahmad Zahir; Muhammad Iqbal; Atif Mehmood; Atif Javed; Azhar Hussain; Bushra; Maqshoof Ahmad (Environmental Monitoring and Assessment, 2021)

Correction to: Assessing the socio-economic viability of solar commercialization and electrification in south Asian countries - Huaping Sun; Rehmat Ullah Awan; Muhammad Atif Nawaz; Muhammad Mohsin; Abdul Khaliq Rasheed; Nadeem Iqbal (Environment, Development and Sustainability, 2021)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

Land-use change affects stoichiometric patterns of soil organic carbon, nitrogen, and phosphorus in the red soil of Southeast China - Xiaojun Yan; Wenhao Yang; Muhammad Atif Muneer; Siwen Zhang; Mingkuang Wang; Liangquan Wu (Journal of Soils and Sediments, 2021)

Correction to: Heterogeneous effects of remittances and institutional quality in reducing environmental deficit in the presence of EKC hypothesis: a global study with the application of panel quantile regression - Muhammad Usman; Atif Jahanger (Environmental Science and Pollution Research, 2021)

Heterogeneous effects of remittances and institutional quality in reducing environmental deficit in the presence of EKC hypothesis: A global study with the application of panel quantile regression - Muhammad Usman; Atif Jahanger (Environmental Science and Pollution Research, 2021)

Co-movement of energy prices and stock market return: environmental wavelet nexus of COVID-19 pandemic from the USA, Europe, and China - FengSheng Chien; Muhammad Sadiq; Hafiz Waqas Kamran; Muhammad Atif Nawaz; Muhammed Sajjad Hussain; Muhammad Raza (Environmental Science and Pollution Research, 2021)

Assessing the socio-economic viability of solar commercialization and electrification in south Asian countries - Huaping Sun; Rehmat Ullah Awan; Muhammad Atif Nawaz; Muhammad Mohsin; Abdul Khaliq Rasheed; Nadeem Iqbal (Environment, Development and Sustainability, 2021)

The impacts of land use/land cover changes on the supply-demand budget of urban ecosystem services - Syed Atif Bokhari; Zafeer Saqib; Amjad Ali; Arif Mahmud; Nadia Akhtar; Ambrina Kanwal; Muhammad Zaman ul Haq (Arabian Journal of Geosciences, 2021)

Geotechnical characterization of bentonite-fly ash mixtures for their application as landfill liner in Pakistan - Hafiz Muhammad Awais Rashid; Arsalan Sardar; Atif Ismail (Arabian Journal of Geosciences, 2021)

Molecular docking of alpha-enolase to elucidate the promising candidates against Streptococcus pneumoniae infection - Muhammad Hassan; Atif Amin Baig; Syed Awais Attique; Shafqat Abbas; Fizza Khan; Sara Zahid; Qurat Ul Ain; Muhammad Usman; Nordin Bin Simbak; Mohammad Amjad Kamal; Hanani Ahmad Yusof (DARU Journal of Pharmaceutical Sciences, 2021)

In vitro differentiation effect of CCL4-induced liver injured mice serum on bone marrow-derived mesenchymal stem cells toward hepatocytes like cells - Sulaiman Shams; Nazia Imran; Sahib Gul Afridi; Muhammad Ayaz; Atif Ali Khan Khalil; Abdul Nasir (Cell and Tissue Banking, 2021)

A feasibility study on microwave imaging of bone for osteoporosis monitoring - Bilal Amin; Atif Shahzad; Lorenzo Crocco; Mengchu Wang; Martin O’Halloran; Ana González-Suárez; Muhammad Adnan Elahi (Medical & Biological Engineering & Computing, 2021)

Assessing the efficiency and total factor productivity growth of the banking industry: do environmental concerns matters? - Faluk Shair; Sun Shaorong; Hafiz Waqas Kamran; Muhammed Sajjad Hussain; Muhammad Atif Nawaz; Van Chien Nguyen (Environmental Science and Pollution Research, 2021)

The dynamic linkage between globalization, financial development, energy utilization, and environmental sustainability in GCC countries - Bo Yang; Atif Jahanger; Muhammad Usman; Muhammad Atif Khan (Environmental Science and Pollution Research, 2021)

Trilemma association of energy consumption, carbon emission, and economic growth of BRICS and OECD regions: quantile regression estimation - Muhammad Atif Nawaz; Muhammed Sajjad Hussain; Hafiz Waqas Kamran; Syed Ehsanullah; Rida Maheen; Faluk Shair (Environmental Science and Pollution Research, 2021)

Nexus between green finance and climate change mitigation in N-11 and BRICS countries: empirical estimation through difference in differences (DID) approach - Muhammad Atif Nawaz; Usha Seshadri; Pranav Kumar; Ramaisa Aqdas; Ataul Karim Patwary; Madiha Riaz (Environmental Science and Pollution Research, 2021)

First report of Curvularia verruculosa causing leaf spot disease of grape (Vitis vinifera) in Afghanistan - Nasir Ahmed Rajput; Hussainullah; Chao Huo; JiFen Cao; Muhammad Atiq; Rana Muhammad Atif; Abdul Mubeen Lodhi; Rehana Naz Syed; Sohaib Sarfraz; Akhtar Hameed; Zhijian Zhao (Journal of Plant Pathology, 2020)

Dietary intake assessment of pyrethroid residues from okra and eggplant grown in peri-urban areas of Punjab, Pakistan - Adnan Amjad; Muhammad Atif Randhawa; Muhammad Sameem Javed; Zafarullah Muhammad; Mussawar Ashraf; Zulfiqar Ahmad; Shamas Murtaza (Environmental Science and Pollution Research, 2020)

Does the inflow of remittances and energy consumption increase CO2 emissions in the era of globalization? A global perspective - Bo Yang; Atif Jahanger; Muhammad Atif Khan (Air Quality, Atmosphere & Health, 2020)

Determinants of farmers’ adaptation to climate change in rain-fed agriculture of Pakistan - Sarah Amir; Zafeer Saqib; Muhammad Irfan Khan; Akhter Ali; Muhammad Azeem Khan; Syed Atif Bokhari; Zaman-ul-Haq (Arabian Journal of Geosciences, 2020)

HPLC-UV characterization, anticholinesterase, and free radical-scavenging activities of Rosa moschata Herrm. leaves and fruits methanolic extracts - Nausheen Nazir; Atif Ali Khan Khalil; Mohammad Nisar; Muhammad Zahoor; Sajjad Ahmad (Brazilian Journal of Botany, 2020)

The impact of airborne pollution and exposure to solar ultraviolet radiation on skin: mechanistic and physiological insight - Atif Ali; Hira Khan; Raheem Bahadar; Asma Riaz; Muhammad Hassham Hassan Bin Asad (Environmental Science and Pollution Research, 2020)

Aluminium oxide nanoparticles inhibit EPS production, adhesion and biofilm formation by multidrug resistant Acinetobacter baumannii - Saima Muzammil; Mohsin Khurshid; Iqra Nawaz; Muhammad Hussnain Siddique; Muhammad Zubair; Muhammad Atif Nisar; Muhammad Imran; Sumreen Hayat (Biofouling, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Spatial analysis of temperature time series over the Upper Indus Basin (UIB) Pakistan - Yasir Latif; Ma Yaoming; Muhammad Yaseen; Sher Muhammad; Muhammad Atif Wazir (Theoretical and Applied Climatology, 2020)
Runoff generated from the Upper Indus Basin (UIB) mainly originates in the massifs of the Hindukush–Karakoram–Himalaya (HKH) region of Pakistan. Water supply in early spring depends upon the snow accumulation in the winter and the subsequent temperature. Seasonal temperature variations corroborate the contemporary dynamics of snow and glaciers. Recently, there has been increasing evidence of accelerated warming in high mountain areas, termed as elevation-dependent warming (EDW). We have identified trends, analyzed inconsistencies, and calculated changes in the maximum, minimum, mean and diurnal temperature range ( T max , T min , T mean , and DTR) at 20 weather stations during four-time series: 1961–2013 (first), 1971–2013 (second), 1981–2013 (third), and 1991–2013 (fourth). We employed the Mann–Kendall test to determine the existence of a trend and Sen’s method for the estimation of prevailing trends, whereas homogeneity analysis was applied before trend identification using three different tests. This study revealed that the largest and smallest magnitudes of trends appeared in the winter and summer, respectively, particularly during the fourth data series. T max revealed robust warming at ten stations, most remarkably at Gupis, Khunjrab, and Naltar at rates of 0.29, 0.36, and 0.43 °C/decade, respectively, during the fourth series. We observed that T min exhibits a mixed pattern of warming and cooling during the second and third series, but cooling becomes stronger during the fourth series, exhibiting significant trends at twelve stations. Khunjrab and Naltar showed steady warming during the fourth series (spring), at rates of 0.26 and 0.13 °C/decade in terms of T mean . The observed decreases in DTR appeared stronger in the fourth series during the summer. These findings tend to partially support the notion of EDW but validate the dominance of cooling spatially and temporally.

Fluorosis and cognitive development among children (6–14 years of age) in the endemic areas of the world: a review and critical analysis - Muhammad Saeed; Riffat Naseem Malik; Atif Kamal (Environmental Science and Pollution Research, 2020)

Synthesis and Application of Titanium Dioxide Nanoparticles for Removal of Cadmium from Wastewater: Kinetic and Equilibrium Study - Muhammad Atif Irshad; Muhammad Bilal Shakoor; Shafaqat Ali; Rab Nawaz; Muhammad Rizwan (Water, Air, & Soil Pollution, 2019)

Anti-pollution cosmetic-based one-step formation of w/o/w multiple emulsion containing D-biotin for skin protection: fabrication and in vitro and in vivo evaluation - Atif Ali; Sajid Iqbal; Aqsa Ilyas; Hira Khan; Muhammad Hassham Hassan Bin Asad; Nighat Fatima; Naveed Akhtar (Drug Delivery and Translational Research, 2019)

Toward GIS-Based Approach for Identification of Ecological Sensitivity Areas: Multi-Criteria Evaluation Technique for Promotion of Tourism in Soon Valley, Pakistan - Muhammad Atif Butt; Khadija Nisar; Syed Amer Mahmood; Javed Sami; Jahanzeb Qureshi; Ghulam Jaffer (Journal of the Indian Society of Remote Sensing, 2019)

Correction to: Sedimentological impact on reservoir quality of Es1 sandstone of Shahejie formation, Nanpu Sag, East China - Muhammad Kashif; Yingchang Cao; Guanghui Yuan; Muhammad Asif; Wang Jian; Wang Zhukhun; Saif Ur Rehman; Atif Zafar; Muhammad Kamran; Orkhan Isgandarov; Asim Falak Naz (Arabian Journal of Geosciences, 2019)

Sedimentological impact on reservoir quality of Es1 sandstone of Shahejie formation, Nanpu Sag, East China - Muhammad Kashif; Yingchang Cao; Guanghui Yuan; Muhammad Asif; Wang Jian; Wang Zhukhun; Saif Ur Rehman; Atif Zafar; Muhammad Kamran; Orkhan Isgandarov; Asim Falak Naz (Arabian Journal of Geosciences, 2019)

Cadmium induces GAPDH- and- MDH mediated delayed cell aging and dysfunction in Candida tropicalis 3Aer - Zaman Khan; Muhammad Atif Nisar; Saima Muzammil; Saima Zafar; Inga Zerr; Abdul Rehman (Environmental Monitoring and Assessment, 2019)

Appraisal of Urban Heat Island Detection of Peshawar Using Land Surface Temperature and Its Impacts on Environment - Rashid Mehmood; Muhammad Atif Butt (Journal of the Indian Society of Remote Sensing, 2019)

Improving the Productivity and Profitability of Late Sown Chickpea by Seed Priming - Muhammad Farooq; Mubshar Hussain; Muhammad Imran; Imran Ahmad; Muhammad Atif; Salem S. Alghamdi (International Journal of Plant Production, 2019)

Glucanolytic Rhizobacteria Produce Antifungal Metabolites and Elicit ROS Scavenging System in Sugarcane - Muhammad Atif Zia; Humaira Yasmin; Faluk Shair; Zahra Jabeen; Saqib Mumtaz; Zafar Hayat; Syed Zia ul Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (Sugar Tech, 2019)

Genome-wide identification and expression analyses of WRKY transcription factor family members from chickpea (Cicer arietinum L.) reveal their role in abiotic stress-responses - Muhammad Waqas; Muhammad Tehseen Azhar; Iqrar Ahmad Rana; Farrukh Azeem; Muhammad Amjad Ali; Muhammad Amjad Nawaz; Gyuhwa Chung; Rana Muhammad Atif (Genes & Genomics, 2019)

Characterization of Cellulose Synthase A (CESA) Gene Family in Eudicots - Muhammad Amjad Nawaz; Xiao Lin; Ting-Fung Chan; Muhammad Imtiaz; Hafiz Mamoon Rehman; Muhammad Amjad Ali; Faheem Shehzad Baloch; Rana Muhammad Atif; Seung Hwan Yang; Gyuhwa Chung (Biochemical Genetics, 2019)

Folate-Functionalized Thiomeric Nanoparticles for Enhanced Docetaxel Cytotoxicity and Improved Oral Bioavailability - Muhammad Sajjad; Muhammad Imran Khan; Sara Naveed; Sana Ijaz; Omer Salman Qureshi; Syed Atif Raza; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2019)

Dielectric properties of bones for the monitoring of osteoporosis - Bilal Amin; Muhammad Adnan Elahi; Atif Shahzad; Emily Porter; Barry McDermott; Martin O’Halloran (Medical & Biological Engineering & Computing, 2019)

Effect of foliar-applied iron complexed with lysine on growth and cadmium (Cd) uptake in rice under Cd stress - Arooj Bashir; Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Wajid Ishaque; Muhammad Atif Riaz; Arosha Maqbool (Environmental Science and Pollution Research, 2018)

Genome-Wide Analysis of Potassium Transport-Related Genes in Chickpea (Cicer arietinum L.) and Their Role in Abiotic Stress Responses - Farrukh Azeem; Bilal Ahmad; Rana Muhammad Atif; Muhammad Amjad Ali; Habibullah Nadeem; Sabir Hussain; Hamid Manzoor; Muhammad Azeem; Muhammad Afzal (Plant Molecular Biology Reporter, 2018)

Correction to: Multi-sensor temporal assessment of tropospheric nitrogen dioxide column densities over Pakistan - Rabbia Murtaza; Muhammad Fahim Khokhar; Asma Noreen; Salman Atif; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2018)

Multi-sensor temporal assessment of tropospheric nitrogen dioxide column densities over Pakistan - Rabbia Murtaza; Muhammad Fahim Khokhar; Asma Noreen; Salman Atif; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2018)

Regenerative Potential of Platelet Rich Fibrin (PRF) for Curing Intrabony Periodontal Defects: A Systematic Review of Clinical Studies - Shariq Najeeb; Zohaib Khurshid; Muhammad Atif Saleem Agwan; Shazia Akhbar Ansari; Muhammad Sohail Zafar; Jukka Pekka Matinlinna (Tissue Engineering and Regenerative Medicine, 2017)

Effect of Rheology and Poloxamers Properties on Release of Drugs from Silicon Dioxide Gel-Filled Hard Gelatin Capsules—A Further Enhancement of Viability of Liquid Semisolid Matrix Technology - Misbah Sultana; Mobashar Ahmad Butt; Tariq Saeed; Rizwan Mahmood; Saeed ul Hassan; Khalid Hussain; Syed Atif Raza; Muhammad Ahsan; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2017)

Prevalence of antibodies to Neospora caninum in the serum of camels (Camelus dromedarius) from central Punjab, Pakistan - Muhammad Mudasser Nazir; Muhammad Oneeb; Muhammad Mazhar Ayaz; Fehmeeda Bibi; Atif Nisar Ahmad; Abdul Waheed; Muhammad Afzal Sajid; Muhammad Tauseef Sultan; Ghulam Yasin; David S. Lindsay (Tropical Animal Health and Production, 2017)

Classification of ankle joint movements based on surface electromyography signals for rehabilitation robot applications - Maged S. AL-Quraishi; Asnor J. Ishak; Siti A. Ahmad; Mohd K. Hasan; Muhammad Al-Qurishi; Hossein Ghapanchizadeh; Atif Alamri (Medical & Biological Engineering & Computing, 2017)

Are Karakoram temperatures out of phase compared to hemispheric trends? - Fayaz Asad; Haifeng Zhu; Hui Zhang; Eryuan Liang; Sher Muhammad; Suhaib Bin Farhan; Iqtidar Hussain; Muhammad Atif Wazir; Moinuddin Ahmed; Jan Esper (Climate Dynamics, 2017)

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil - Mahnaz Roohi; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Muhammad Arslan Ashraf; Muhammad Atif Riaz; Ishaq A. Mian (Environmental Science and Pollution Research, 2017)

TK1656, an L-asparaginase from Thermococcus kodakarensis, a novel candidate for therapeutic applications - Shahid Mahmood Chohan; Muhammad Atif Nisar; Naeem Rashid; Ghazaleh Gharib; Qamar Bashir; Masood Ahmed Siddiqui (Biologia, 2016)

The impact of seasonal variation on organochlorine pesticide residues in buffalo and cow milk of selected dairy farms from Faisalabad region - Muhammad Wasim Sajid; Muhammad Shamoon; Muhammad Atif Randhawa; Muhammad Asim; Abdul Shakoor Chaudhry (Environmental Monitoring and Assessment, 2016)

Rice (Oryza sativa L.) hydraulic conductivity links to leaf venation architecture under well-watered condition rather than PEG-induced water deficit - Muhammad Adnan Tabassum; Yuhui Ye; Tingting Yu; Guanglong Zhu; Muhammad Shahid Rizwan; Muhammad Atif Wahid; Shaobing Peng; Yong Li (Acta Physiologiae Plantarum, 2016)

Correlation of Arsenic Levels in Smokeless Tobacco Products and Biological Samples of Oral Cancer Patients and Control Consumers - Sadaf S. Arain; Tasneem G. Kazi; Hassan I. Afridi; Farah N. Talpur; Atif G. Kazi; Kapil D. Brahman; Naeemullah; Abdul H. Panhwar; Muhammad A. Kamboh (Biological Trace Element Research, 2015)

Antimicrobial and inhibition on heat-induced protein denaturation of constituents isolated from Polygonatum verticillatum rhizomes - Haroon Khan; Muhammad Saeed; Abdur Rauf; Muhammad Atif Khan; Naveed Muhammad (Natural Product Research, 2015)

Crossability among modern roses and heterosis of quantitative and qualitative traits in hybrids - Muhammad Nadeem; Adnan Younis; Atif Riaz; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2015)

A Question Mark on Iron Deficiency in 185 Million People of Pakistan: Its Outcomes and Prevention - Anwaar Ahmed; Asif Ahmad; Nauman Khalid; Angel David; Mansoor Abdullah Sandhu; Muhammad Atif Randhawa; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2014)

Pre-planting exogenous application of gibberellic acid influences sprouting, vegetative growth, flowering, and subsequent bulb characteristics of ‘Ad-Rem’ tulip - Fahad Ramzan; Adnan Younis; Atif Riaz; Sajid Ali; Muhammad Irfan Siddique; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2014)

Flowering time in wheat (Triticum aestivum L.): a key factor for global adaptability - Atif Kamran; Muhammad Iqbal; Dean Spaner (Euphytica, 2014)

A Question Mark on Zinc Deficiency in 185 Million People in Pakistan—Possible Way Out - Nauman Khalid; Anwaar Ahmed; Muhammad Shahbaz Bhatti; Muhammad Atif Randhawa; Asif Ahmad; Rabab Rafaqat (Critical Reviews in Food Science and Nutrition, 2014)

Microsatellite analysis of Rosa damascena from Pakistan and Iran - Amjad Farooq; Mahnaz Kiani; Muhammad Aslam Khan; Atif Riaz; Asif Ali Khan; Natalie Anderson; David H. Byrne (Horticulture, Environment, and Biotechnology, 2013)

Black Pepper and Health Claims: A Comprehensive Treatise - Masood Sadiq Butt; Imran Pasha; Muhammad Tauseef Sultan; Muhammad Atif Randhawa; Farhan Saeed; Waqas Ahmed (Critical Reviews in Food Science and Nutrition, 2013)

Aflatoxins: Biosynthesis, Occurrence, Toxicity, and Remedies - Muhammad Abrar; Faqir Muhammad Anjum; Masood Sadiq Butt; Imran Pasha; Muhammad Atif Randhawa; Farhan Saeed; Khalid Waqas (Critical Reviews in Food Science and Nutrition, 2013)

Sequence determination of a quadripartite dsRNA virus isolated from Aspergillus foetidus - Zisis Kozlakidis; Noemi Herrero; Selin Ozkan; Lakkhana Kanhayuwa; Atif Jamal; Muhammad F. Bhatti; Robert H. A. Coutts (Archives of Virology, 2013)

Incidence of dsRNA Mycoviruses in a Collection of Aspergillus fumigatus Isolates - Muhammad F. Bhatti; Atif Jamal; Elaine M. Bignell; Michael A. Petrou; Robert H. A. Coutts (Mycopathologia, 2012)

RETRACTED ARTICLE: Bovine viral diarrhea virus nonstructural protein 5A is phosphorylated by cdc2 cyclin-dependent kinase in vitro - Muhammad Atif Zahoor; Saima Naim; Guangai Xue; Mariluz Arainga Ramirez (Archives of Virology, 2012)

Characterization and application of monoclonal antibodies to bovine viral diarrhea virus nonstructural protein 5A - Muhammad Atif Zahoor; Daisuke Yamane; Yassir Mahgoub Mohamed; Kyousuke Kobayashi; Kentaro Kato; Yukinobu Tohya; Hiroomi Akashi (Archives of Virology, 2009)

Activation of extracellular signal-regulated kinase in MDBK cells infected with bovine viral diarrhea virus - Daisuke Yamane; Muhammad Atif Zahoor; Yassir Mahgoub Mohamed; Walid Azab; Kentaro Kato; Yukinobu Tohya; Hiroomi Akashi (Archives of Virology, 2009)

The microbiological hydroxylation of levonorgestrel - Muhammad Iqbal Choudhary; Muhammad Atif Sarfraz; A. Nawaz; Muhammad Qaiser Fatmi; Atta-Ur-Rahman (Natural Product Research, 2006)

Production and characterization of a highly active cellobiase from Aspergillus niger grown in solid state fermentation - Muhammad Ibrahim Rajoka; Muhammad Waheed Akhtar; Atif Hanif; A. M. Khalid (World Journal of Microbiology and Biotechnology, 2006)